Oral manifestations of Diabetes Mellitus in the elderly: an integrative review (Research, Society and Development, 2022)
Objective: This study aims to identify the association between oral manifestations and Diabetes Mellitus in the elderly. Methodology: This is an integrative literature review carried out through a search strategy in the LILACS, PubMed, Scopus and Web of Science databases. In the search process, the descriptors “Elderly”, “Diabetes Mellitus”, “Oral Health”, “Aged”, “Elderly” and “Oral Health” were used, combined with the Boolean operator “AND”.  Results: A total of 1,747 studies were found, of which 12 were selected. Among the oral manifestations in elderly diabetics, periodontal diseases, dental caries, edentulism, xerostomia and the need for dental prosthesis stand out. Conclusion: It is concluded that there is a need for the dentist to act in the control of oral manifestations and oral health care of diabetic elderly.